Criteria of the State External Debt Load: Methodological Aspect. (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article analyzes loan capitals international markets, the level and dynamics of the external debt burden of different countries. It also considers the necessity and expediency of national economies external borrowings. The current methodology for assessing external debt level has been reviewed.The necessity of debt burden constant monitoring both by the creditor and the borrower has been substantiated. The system of external debt private indices for the debtor, that gives objective assessment of the country’s debt burden, perspectives for external borrowings and debt obligations fulfillment have been elaborated.The article gives an additional list of private indices for the country’s external debt assessment, they are: the ratio of the surplus product to the required; external borrowings share for the economy real sector; the amount of aggregate and external debt per employee.
Keywords: gross external debt, debt load, debt assessment criteria, methodological tools, loan market, lender, borrower, debt management.